2012
DOI: 10.1016/j.actamat.2011.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Ballistic performance of nanocrystalline and nanotwinned ultrafine crystal steel

Abstract: Because of their remarkable mechanical properties, nanocrystalline metals have been the focus of much research in recent years. Refining their grain size to the nanometer range (<100 nm) effectively reduces their dislocation mobility, thus achieving very high yield strength and surface hardness-as predicted by the Hall-Petch relation-as well as higher strain-rate sensitivity. Recent works have additionally suggested that nanocrystalline metals exhibit an even higher compressive strength under shock loading. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(33 citation statements)
references
References 56 publications
0
33
0
Order By: Relevance
“…Here, the cohesive strength is modeled by Weibull A bilinear cohesive law has two important parameters, namely the cohesive strength T 0 n and fracture energy G IC . The fracture energy of the CG 304 SS is obtained from [46]. The flow stress of the CG specimen is from the experiments [46], while that of the NGL is estimated from experiments of the SMATed 316L SS [47].…”
Section: Weibull Random Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, the cohesive strength is modeled by Weibull A bilinear cohesive law has two important parameters, namely the cohesive strength T 0 n and fracture energy G IC . The fracture energy of the CG 304 SS is obtained from [46]. The flow stress of the CG specimen is from the experiments [46], while that of the NGL is estimated from experiments of the SMATed 316L SS [47].…”
Section: Weibull Random Fieldmentioning
confidence: 99%
“…Young's modulus E and Poisson's ratio v of both the CG and the NGL are taken as 200 GPa and 0.33, respectively [46]. The flow stress of the CG specimen is from the experiments [46], while that of the NGL is estimated from experiments of the SMATed 316L SS [47]. The kinematic hardening model is used to describe the cyclic plastic behavior of the metals.…”
Section: D Cfe Geometric Modeling and Quantification Of Constitutivementioning
confidence: 99%
“…Recent experiments and theoretical models have shown that the HTS with the secondary twins at the nanoscale can be a novel nanostructured design to achieve higher strength and toughness both under conventional deformation conditions and under extreme deformation conditions. 16,[36][37][38][39] So, it is highly desirable to examine the microstructure evolutions and underlying physics of deformation mechanisms for hierarchically NT fcc metals with low SFEs subjected to shock loading. In this regard, the focus of this paper is to understand the effect of spacing of secondary twins on the strength behind the shock front, spall strength, and related atomic-level deformation mechanisms in hierarchically NT Ag (a model material with low SFE) subjected to shock loading using MD simulations.…”
Section: Introductionmentioning
confidence: 99%
“…The fitting parameters for 316L, obtained by Olleak, A. et al (2015), was also included in the table below so that a comparison between the material properties of these two different grades of stainless steel could be made. The fitting parameters obtained by Frontán, J. et al (2012) matched those obtained by Krasauskas, P. et al (2015). Thus, 304 Stainless Steel III could be ignored from the analysis since it was already represented by 304 Stainless Steel I.…”
Section: Figure B14 -View Of Force Reaction Probe Settingsmentioning
confidence: 49%
“…In order to evaluate the influence that the fitting parameters from the Johnson-Cook material model had on the stress-strain curve for 304 stainless steel, the fitting parameters obtained by Frontán, J. et al (2012) was compared to that obtained by Mori, L. et al (2007) and Krasauskas, P. et al (2015). These fitting parameters can be found in the table below.…”
Section: Figure B14 -View Of Force Reaction Probe Settingsmentioning
confidence: 99%